DDR1 and MT1-MMP Expression Levels Are Determinant for Triggering BIK-Mediated Apoptosis by 3D Type I Collagen Matrix in Invasive Basal-Like Breast Carcinoma Cells - Saby, Charles; Collin, Guillaume; Sinane, Maha; Buache, Emilie; Van Gulick, Laurence; Saltel, Frédéric; Maquoi, Erik; Morjani, Hamid (Frontiers in Pharmacology, 2019)
Type I collagen is the major adhesive component in breast interstitial stroma which represent the first stromal barrier against tumor invasion. We have previously shown that type I collagen activates DDR1 which plays a key role in cell growth suppression and BIK-induced apoptosis in non-invasive luminal-like breast carcinoma cells. We have also shown that MT1-MMP is able to rescue these cells and protect them against apoptosis suggesting a degradation of type I collagen and/or DDR1 cleavage by MT1-MMP. Decreased DDR1 expression has been associated with the epithelial to mesenchymal transition process in breast cancer. In the present work, we propose to study the role of MT1-MMP in the protection of basal-like MDA-MB-231 carcinoma against BIK associated apoptosis. We aimed to investigate whether MT1-MMP depletion is able to restore apoptosis, and to verify if such depletion is able to restore full length DDR1 expression and phosphorylation. Sh-RNA strategy against MT1-MMP mRNA was able to restore relatively full length DDR1 expression and phosphorylation. This was accompanied by a decrease in cell growth and an overexpression of BIK. This suggested that MT1-MMP expression in these cells probably protects these cells against tumor suppression and apoptosis via DDR1 cleavage. Since DDR1 was moderately expressed in MDA-MB-231 cells, we then investigated whether overexpression of DDR1 could increase cell growth suppression and apoptosis. Data showed that overexpression of DDR1 increased cell growth and increased BIK expression, suggesting that moderate expression level of full length DDR1 in basal-like breast carcinoma provides them with a capacity to resist to cell growth suppression and collagen-induced apoptosis. Finally, overexpression of DDR1 and MT1-MMP depletion in MDA-MB-231 cells increased in a synergistic way collagen-induced cell growth suppression and apoptosis. Taken together, our data suggest that during the acquisition of mesenchymal features, the low level of DDR1 expression should be considered as an important biomarker in the prognosis of basal-like breast carcinoma, conferring a high rate of cell growth and protection against collagen-induced apoptosis.